Persistence of bactericidal antibodies following early infant vaccination with a serogroup B meningococcal vaccine and immunogenicity of a preschool booster dose - Snape, M; Saroey, P; John, T; Robinson, H; Kelly, S; Gossger, N; Yu, L; Wang, H; Toneatto, D; Dull, P; Pollard, A (Canadian Medical Association, 2013)
Background: The multicomponent serogroup B meningococcal (4CMenB) vaccine was recently licensed for use in Europe. There are currently no data on the persistence of bactericidal antibodies induced by use of this vaccine in infants. Our objective was to evaluate serogroup B–specific bactericidal antibodies in children aged 40–44 months previously vaccinated at 2, 4, 6 and 12 months of age. Methods: Participants given 4 doses of 4CMenB as infants received a fifth dose of the vaccine at 40–44 months of age. Age-matched participants who were MenB vaccine–naive received 4CMenB and formed the control group. We evaluated human complement serum bactericidal activity (hSBA) titres at baseline and 1 month after each dose of 4CMenB. Results: Before a booster dose at enrolment, 41%–76% of 17 participants previously vaccinated with 4CMenB in infancy had hSBA titres of 4 or greater against 4 reference strains. Before vaccination in the control group (n = 40) these proportions were similar for strains 44/76-SL (63%) and M10713 (68%) but low for strains NZ98/254 (0%) and 5/99 (3%). A booster dose in the 4CMenB-primed participants generated greater increases in hSBA titres than in controls. Interpretation: As has been observed with other meningococcal vaccines, bactericidal antibodies waned after vaccination with 4CMenB administered according to an approved infant vaccination schedule of 2, 4, 6 and 12 months of age, but there was an anamnestic response to a booster dose at 40–44 months of age. If 4CMenB were introduced into routine vaccination schedules, assessment of the need for a booster dose would require data on the impact of these declining titres on vaccine effectiveness. ClinicalTrials.gov, no. NCT01027351